Stand up! Speak up! : a story inspired by the Climate Change Revolution - Joyner, Andrew (Illustrator) (Schwartz & Wade Books, 2020)
Celebrate young climate change activists in this charming story about an empowered girl who shows up, listens up, and ultimately, speaks up to inspire her community to take action against climate change. After attending a climate march, a young activist is motivated to make an effort and do her part to help the planet... by organizing volunteers to work to make green changes in their community, from cleaning a lake, to planting trees, to making composting bins, to hosting a clothing swap and more! Here is an uplifting picture book that is an important reminder that no change is too small--and no person is too young--to make a difference.